Decision-making factors influencing land use transformation and its implication on forest landscape restoration in Ethiopia - Shibire Bekele Eshetu; Stefan Sieber; Marcos Lana; Katharina Löhr (Journal of Land Use Science)
Macro-level landscape patterns are often a result of a strong influence on human decisions at the micro level. The abilities and objectives of decision-makers should be explicitly addressed to improve our understanding of land use transformation. This research explores the factors influencing smallholder farmers to transform their land use while implementing Forest Landscape Restoration (FLR). We employed a systematic sampling technique to select a study catchment in Southern Ethiopia and 228 households were randomly approached for a household survey. Reaping more economic benefits is the most contributing factor for land use transformation in the study region. Land use transformation towards FLR options such as woodlot and agroforestry is substantially influenced by the location of the farm within the catchment. Furthermore, the study reveals that land allocated for different land uses differs across farmers depending upon their change orientation behaviours categorized as survivalist, subsistence-oriented and market-orientated smallholder farmers. When carrying out FLR in the study region and in similar landscapes that aim to engage smallholder farmers, it is important to promote fast-growing economically rewarding tree species.